Atorvastatin attenuates the ovarian damage induced by cyclophosphamide in rat: An experimental study - Maedeh Hamzeh; Seyed Jalal Hosseinimehr; Hamid Reza Mohammadi; Saeed Yaghubi Beklar; Ayat Dashti; Fereshteh Talebpour Amiri (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Cyclophosphamide (CP), as an anticancer agent, causes ovarian toxicity and subsequent infertility in women. Atorvastatin (ATV) at a low dose has antioxidant and anti-inflammatory properties. Objective: The aim of this study was to investigate the protective effect of ATV against CP-induced ovarian injury in rat. Materials and Methods: In this experimental study, thirty-two female Wistar rats were randomly divided into four groups as I) control, II) ATV (10 mg/kg), III) CP (150 mg/kg), and IV) CP +ATV. The ATV treated groups were received ATV for 10 days via oral gavage. In the CP+ATV group, ATV was administrated on 5 days before and 5 days after CP injection. Histological structure, apoptosis (caspase-3), oxidative stress parameters as malondialdehyde, reactive oxygen species, protein carbonyl levels and cell viability were evaluated in ovary tissue by histological scores, immunohistochemistry, histochemical and biochemical assays. The levels of estrogen and progesterone hormones were measured on the 12th day of study. Results: ATV pretreatment significantly decreased the levels of oxidative stress biomarkers as malondialdehyde, reactive oxygen species and protein carbonyl levels and increased cell death in CP-treated rats as compared with the CP alone group. ATV significantly increased estrogen and progesterone levels in CP-treated rats. In addition, the histological examination showed ATV mitigated acute inflammation, degenerative cells in stroma and follicles, stromal edema, vacuolization, atresia of the follicles and congestion of blood vessels in the CP-treated animals. Furthermore, ATV significantly reduced immunoreactivity level of caspase-3 in CP-treated rats. Conclusion: Our results showed that the ATV with antioxidant and anti-apoptosis (caspase-3) activities protected ovarian against CP-induced toxicity.